A impossibilidade de indenização punitiva no direito brasileiro como vontade incontestável do legislador - Sousa, Alexandre Castro (2022)
The aim of this study is to defend the impossibility of punitive damages in Brazilian law, as this is the undisputed will of the legislator. The main issue presented is that there is no agreement on the matter between the Legislative and the Judiciary powers and, for this reason, it is argued that the understanding that should prevail is the one that represents the will of the people, since, in democracy, the legislator has the final word on the matter. Therefore, enough elements are addressed for the study of the legal order and system, especially about the application, integration and correction of the law and about the functions of civil liability and moral damage, so it can defend the impossibility of punitive damages, whether by the will of the legislative or by the inconsistencies of the institute within the legal system